Should applicants to Nottingham University Medical School study a non-science A-level?: a cohort study - Yates, Janet; Smith, Jennifer; James, David; Ferguson, Eamonn (BioMed Central, 2009)
Background It has been suggested that studying non-science subjects at A-level should be compulsory for medical students. Our admissions criteria specify only Biology, Chemistry and one or more additional subjects. This study aimed to determine whether studying a non-science subject for A-level is an independent predictor of achievement on the undergraduate medical course.